Adsorption Thermodynamics of Carbaryl onto Four Texturally Different Indian Soils - R.P. Singh; Sujata Singh; Garima Srivastava (Adsorption Science & Technology)
The adsorption thermodynamics of carbaryl onto four divergent textured Indian soils from methanol/water mixtures (f s = 0.1) have been investigated at 25 °C and 50 °C via adsorption isotherms, the Freundlich equation, distribution coefficient measurements and thermodynamic parameters. The measured equilibrium adsorption isotherms were L-shaped for all four soils at both temperatures. The adsorption of carbaryl onto all four soils increased with increasing temperature. The highest adsorption was observed on F.R.I. silt loam (FSL) followed by Alampur silt loam (ASL), Kalai loam (KL) and Bhoran sandy loam (BSL) soils at both temperatures, as anticipated from the values of the Freundlich constant, K F , and the distribution coefficient, K D . The affinity of carbaryl towards the organic carbon, organic matter and clay content of the soils was evaluated from calculations of the values of K OC and K OM . The predicted values of log K OM were also evaluated by using the aqueous solubility, the 1-octanol/water partition coefficient (K OW ), the adsorbability index (AI) and the first-order molecular connectivity index ( 1 χ) of carbaryl. Use of the AI and 1 χ indices of carbaryl gave predicted log K OM values close to those observed experimentally. The thermodynamic equilibrium constant (K 0 ), the standard free energy (ΔG 0 ), the standard enthalpy change (ΔH 0 ) and the standard entropy change (ΔS 0 ) were all calculated in order to predict the nature of the adsorption process.